The Social Stigma of Mental Illness and Its Impact on the Patient and Their Family: Theoretical Analytical Study - Alzahmi, Amna; Maya , Roula (Al-Adab Journal, 2025)
This study addresses the concept of social stigma associated with mental illness and its impact on patients and their families, in the context of the increasing prevalence of these disorders globally. The study aimed to explore the concept of social stigma, its patterns, and to understand mental illness and its causes, while examining the social repercussions faced by individuals suffering from mental disorders. It also sought to uncover the strategies that families can adopt to combat this stigma. The study employed a descriptive approach to collect and analyze data related to these phenomena.The results revealed that social stigma intensifies feelings of isolation and negatively affects social interaction, hindering recovery efforts. It particularly affects family members, who may experience psychological stress due to the stigma attached to their ill relatives, which may lead to delays in seeking treatment and, consequently, result in the worsening of the condition. The study recommended the elimination of negative terminology, raising public awareness through awareness campaigns, and enacting laws to protect patients' rights. Additionally, it highlighted the importance of supporting families and empowering them to provide the necessary care to their loved ones by offering appropriate information and resources.This research is considered a valuable contribution to enhancing understanding and awareness of mental health issues, contributing to improving the quality of life for affected individuals and their families.